Mon4Aware: A multi-objective and context-aware approach to decompose monolithic applications - Urdangarin, Roger Gonçalves; Farias, Kleinner; Barbosa, Jorge (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2021: Anais do XVII Simpósio Brasileiro de Sistemas de Informação, 2021)
This article introduces Mon4Aware, a multi-objective and context-aware approach to decompose monolithic applications. Mon4Aware stands out for: (1) using optimization based on multiple criteria to allow monolithic applications to be modularized in different ways, making its decomposition process flexible; and (2) to propose a context meta-model to allow the decomposed modules of the monolithic application to be able to adapt under certain contextual situations. Software developers can use Mon4Aware as a guide to modernization activities for monolithic applications, making them less error-prone. The approach was evaluated through a case study, in which the conceptual viability of Mon4Aware was demonstrated, as well as promising initial results in generating recommendations for the decomposition of monolithic applications.